Local Wisdom Videos Boost Elementary Social Studies Outcomes in Indonesia: Video Kearifan Lokal Dongkrak Hasil Belajar IPS SD di Indonesia - Arifin, Akhmad Samsul; Wachidah, Kemil (Inquest Journal, 2025)
This study addresses the issue of low learning outcomes and student disengagement in fourth-grade social studies, where traditional teaching methods fail to capture student interest, resulting in passive participation. The aim was to assess the impact of video learning media on students' cognitive learning outcomes. Employing a quantitative experimental approach with a one-group pretest-posttest design and saturated sampling, data were collected via pretests and posttests. Findings indicated a significant improvement in cognitive learning outcomes post-intervention with video media. The study concludes that video-based learning media, incorporating local wisdom, effectively enhances cognitive learning outcomes in fourth-grade social studies students.